2019
DOI: 10.1111/plb.13027
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics ofEchinops gmeliniiTurcz. at different successional stages of biological soil crusts in a temperate desert in China

Abstract: The effects of biological soil crusts (BSC) on vascular plant growth can be positive, neutral or negative, and little information is available on the impacts of different BSC successional stages on vascular plant population dynamics.• We analysed seedling emergence, survival, plant growth and reproduction in response to different BSC successional stages (i.e. habitats: bare soil, cyanobacteria, lichen and moss crusts) in natural populations of Echinops gmelinii Turcz. in the Tengger Desert of northwest China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The plant mortality was recorded every three days in all treatments from April to July. Our field investigation of E. gmelinii population for three years (2016 to 2018) showed that less than 30% of seedlings could successfully overwinter in our study area (Wang et al, 2019b). Thus, survival of overwintered seedlings is a key factor for affecting population dynamics of E. gmelinii .…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The plant mortality was recorded every three days in all treatments from April to July. Our field investigation of E. gmelinii population for three years (2016 to 2018) showed that less than 30% of seedlings could successfully overwinter in our study area (Wang et al, 2019b). Thus, survival of overwintered seedlings is a key factor for affecting population dynamics of E. gmelinii .…”
Section: Methodsmentioning
confidence: 87%
“…E. gmelinii seeds germinate in summer and autumn, and plants overwinter as rosettes and complete their life cycle quickly by utilizing spring and early summer rainfall (Wang et al, 2019a), which could avoid resource competition with other summer annuals (Tobe, Zhang & Omasa, 2005). At a field site in the Tengger Desert, we found that the population dynamics of E. gmelinii were very sensitive to rainfall variation (Wang et al, 2019b); thus, the species may be particularly threatened by climate change. Furthermore, E. gmelinii provides an ideal opportunity to understand the response of the life history adaptation strategies of winter annuals in temperate desert to rainfall variation in the context of global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…E. gmelinii seeds germinate in summer and autumn, and plants overwinter as rosettes and complete their life cycle quickly by utilizing spring and early summer rainfall (Wang et al 2019a), which could avoid resource competition with other summer annuals (Tobe et al 2005). At a field site in the Tengger Desert, we found that the population dynamics of E. gmelinii were very sensitive to rainfall variation (Wang et al 2019b); thus, the species may be particularly threatened by climate change.…”
Section: Introductionmentioning
confidence: 83%
“…However, due to the long growth cycle, sparse branches and leaves of walnut and Zanthoxylum bungeanum trees, the interception effect of rainfall infiltration and runoff erosion is limited. [36] At the same time, owing to their strong nutrient plunder in the soil to make it difficult for the shrubs and grasses under the trees to survive, it is very easy to cause large area of surface exposure, everserious soil erosion and underground leakage, which further induces the formation of rocky desertification [37]. With its high compatibility with different types of habitats and strong stress resistance, BSCs can directly absorb water and nutrients from the body surface through special physiological structure and root system to promote the accumulation of nutrient content in soil, and effectively improve soil physical and chemical properties, so as to maintain the dynamic balance of karst soil system [38].…”
Section: Control Of Rocky Desertificationmentioning
confidence: 99%